Application of Vibrational Methods in Wood Performance Testing: A Short Review - Jiawen Shi; Shiyan Yin; Wenlan Huang; Bin Na (BioResources)
Vibrational methods, which are widely recognized non-destructive testing (NDT) techniques for timber, have garnered significant attention due to their ease of use, broad applicability, and reliable data output. These methods analyze the vibrational response of wood to external stimuli to assess its mechanical properties and internal structure. With advancements in sensor technology, signal processing, and computer simulation, the role of the vibrational methods in timber inspection has been largely expanded, enhancing both the scientific application and quality assurance of timber. This paper provides a comprehensive review of applications of vibrational methods in timber performance evaluation, focusing on its vibrational characteristics, underlying principles, and utility in detecting the physical and mechanical properties as well as internal defects of timber. Furthermore, potential future trends are discussed. Through analysis and research, valuable insights into the evolution of non-destructive timber testing technology are aimed to be provided by this review, and technological innovation in the timber industry is encouraged.